EVALUASI RANCANG BANGUN TERKAIT PENGADAAN FASILITAS LINGKUNGAN PADA RUMAH SUSUN LOKBIN RAWA BUAYA, JAKARTA BARAT - Asri Ardiati Sunoto (Jurnal Arsitektur ZONASI, 2022)
Abstract: To support the implementation of housing development for middle to lower economic class people and structuring slum areas, the Government of DKI Jakarta has built many flats, including the Lokbin Rawa Buaya Flat located in Cengkareng, West Jakarta. The provision of flat facilities generally does not accommodate the physical, social and psychological needs of the occupants. Therefore, this study aims to evaluate the Lokbin Rawa Buaya Flats' design regarding their facilities. The indicators used as a reference for evaluation based on SNI 03-1733-2004 (Indonesia standard) as well as the design criteria for public and social facilities based on user characteristics (intended primary to disable and women). The post-occupancy evaluation was also carried out in this study. In general, this research concludes that there are facilities based on SNI 03-1733-2004 that are not met, but there are also facilities that are available beyond the standard. While the evaluation refers to the design criteria of facilities based on the user characteristics concludes that several design criteria are met and there are also design criteria that are not met with the facilities provided. Meanwhile, based on post-occupancy evaluation some activities are carried out not in the space provided. The cause is beside the capacity of the space provided is not enough but also because facilities are not available. These findings indicate that in the procurement of facilities, reference to space standards alone is not enough, there needs adaptation and adjustment process for the users and building authority in managing the Flats.Keywords: Flats; Design evaluation; FacilitiesAbstrak: Dalam rangka mendukung pelaksanaan pembangunan perumahan bagi masyarakat golongan ekonomi menengah ke bawah dan penataan kawasan kumuh, Pemerintah DKI Jakarta membangun banyak rumah susun, diantaranya Rumah Susun Lokbin Rawa Buaya di Cengkareng, Jakarta Barat. Penyediaan fasilitas rumah susun umumnya kurang mengakomodir kebutuhan fisik sosial maupun psikologis penghuninya. Oleh karena itu dalam penelitian ini diadakan evaluasi desain Rumah Susun Lokbin Rawa Buaya dari segi pengadaan sarana lingkungan. Indikator yang digunakan sebagai acuan adalah dari SNI 03-1733-2004 dan kriteria rancangan fasilitas umum dan sosial berdasarkan karakteristik pengguna serta evaluasi pasca huni. Penelitian ini menghasilkan kesimpulan bahwa ada sarana lingkungan berdasarkan standar SNI 03-1733-2004 tidak terpenuhi, namun ada juga sarana lingkungan yang melampaui standar. Sedangkan evaluasi berdasarkan kriteria rancangan sarana lingkungan berdasarkan karakteristik pengguna disimpulkan ada beberapa kriteria rancangan yang terpenuhi dan ada pula yang tidak terpenuhi. Sementara berdasarkan evaluasi pasca huni terdapat kegiatan yang dilakukan tidak pada ruang yang disediakan. Penyebabnya adalah selain karena kapasitas ruang yang disediakan kurang namun juga karena sarana lingkungan tidak tersedia. Temuan ini menunjukkan bahwa dalam pengadaan sarana lingkungan, acuan standar ruang saja tidak cukup, perlu pengaturan dan proses adaptasi dari pihak pengguna dan pengelola bangunan dalam mengelola bangunan rusun.Kata kunci: Evaluasi Rancang Bangun, Rumah susun, Sarana Lingkungan